Optimal Financial Contracting: Debt versus Outside Equity - Fluck, Zsuzsanna (Review of Financial Studies, 1998)
Journal Article Optimal Financial Contracting: Debt versus Outside Equity Get access Zsuzsanna Fluck Zsuzsanna Fluck New York University Address correspondence to Zsuzsanna Fluck, Department of Finance, Stern School of Business, New York University, 44 West 4th Street, Suite 9-190, New York, NY 10012, or e-mail: zfluck@stern.nyu.edu. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 11, Issue 2, April 1998, Pages 383–418, https://doi.org/10.1093/rfs/11.2.383 Published: 03 June 2015